2020
DOI: 10.31699/ijcpe.2020.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study for Assessment of Cutting Density Effect on Hole Cleaning Efficiency in Inclined and Horizontal Wells

Abstract: The poor hole cleaning efficiency could causes many problems such as high torque, drag, poor hydraulics and pipe stuck. These inherent problems result in an avoidable high operation cost which this study tried to address.  In this study, the effect of cutting density on hole cleaning efficiency in deviated and horizontal wells was investigated. Experiments were conducted using 40 feet (12 m) long of flow loop made from iron and PVC. However, the test section was made from PVC with (5.1m) long and (4” ID) for o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Also, Hydraulic Calculations with Excel is an easy-to-use tool specifically designed to help calculate pressure drop and flow characteristics. Since it is an Excel spreadsheet, entering data is all it does and let this tool do the rest by using equations from 1 to 10 as in Figure (6), Table (4) includes field data used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Hydraulic Calculations with Excel is an easy-to-use tool specifically designed to help calculate pressure drop and flow characteristics. Since it is an Excel spreadsheet, entering data is all it does and let this tool do the rest by using equations from 1 to 10 as in Figure (6), Table (4) includes field data used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is better to use drilling fluids with a low solid content, such as polymeric drilling fluids [3]. Oil and water are in some cases ideal drilling fluids for drilling the ground layers with low pressure [4]. Low solids drilling mud is a drilling fluid that contains less solids than conventional mud with the same density and parallel use [5].…”
Section: Introductionmentioning
confidence: 99%
“…Te results of the study indicate that annular velocity is crucial in improving CTR and that CTR ensures efcient cleaning under diferent drilling scenarios, including varying inclinations, sizes, and shapes of cuttings. In this study, CTR was computed as the ratio of collected dry cuttings to the fnal total dry cuttings collected [189]. Ahmed et al provided a numerical model to compute the important parameters for hole cleaning and provided an engineering methodology to consider hole enlargement by using a Monte Carlo simulator.…”
Section: Rheology Modeling Factors Indicators Experiments Andmentioning
confidence: 99%
“…Early's earlier study (Sinitsyn & Viktorova, 1968) concluded that MoS 2 has greater antifriction properties for Si and calcium-complex while denoting 30% more efficiency for Li grease than graphite. MoS 2 has a layer lattice structure, and the atoms in each layer or "basal plane" are positioned at the corners of regular hexagons, leading to higher load-carrying capacity (Mohammed, 2013). Meanwhile, combining MoS 2 with graphite at a 60:40 ratio has a synergetic effect in increasing the weld load by 120 kg while decreasing the wear scar diameter by 22% (Antony et al, 1994).…”
Section: Explanationmentioning
confidence: 99%